Resistin in idiopathic inflammatory myopathies - Filková, Mária; Hulejová, Hana; Kuncová, Klára; Pleštilová, Lenka; Cerezo, Lucie Andrés; Mann, Heřman; Klein, Martin; Zámečník, Josef; Gay, Steffen; Vencovský, Jiří; Senolt, Ladislav (Arthritis research & therapy, 2012)
INTRODUCTION: The purpose of this study was to evaluate and compare the serum levels and local expression of resistin in patients with idiopathic inflammatory myopathies to controls, and to determine the relationship between resistin levels, inflammation and disease activity. METHODS: Serum resistin levels were determined in 42 patients with inflammatory myopathies and 27 healthy controls. The association among resistin levels, inflammation, global disease activity and muscle strength was examined. The expression of resistin in muscle tissues from patients with inflammatory myopathies and healthy controls was evaluated. Gene expression and protein release from resistin-stimulated muscle and mononuclear cells were assessed. RESULTS: In patients with inflammatory myopathies, the serum levels of resistin were significantly higher than those observed in controls (8.53 ± 6.84 vs. 4.54 ± 1.08 ng/ml, P < 0.0001) and correlated with C-reactive protein (CRP) levels (r = 0.328, P = 0.044) and myositis disease activity assessment visual analogue scales (MYOACT) (r = 0.382, P = 0.026). Stronger association was observed between the levels of serum resistin and CRP levels (r = 0.717, P = 0.037) as well as MYOACT (r = 0.798, P = 0.007), and there was a trend towards correlation between serum resistin and myoglobin levels (r = 0.650, P = 0.067) in anti-Jo-1 positive patients. Furthermore, in patients with dermatomyositis, serum resistin levels significantly correlated with MYOACT (r = 0.667, P = 0.001), creatine kinase (r = 0.739, P = 0.001) and myoglobin levels (r = 0.791, P = 0.0003) and showed a trend towards correlation with CRP levels (r = 0.447, P = 0.067). Resistin expression in muscle tissue was significantly higher in patients with inflammatory myopathies compared to controls, and resistin induced the expression of interleukins (IL)-1β and IL-6 and monocyte chemoattractant protein (MCP)-1 in mononuclear cells but not in myocytes. CONCLUSIONS: The results of this study indicate that higher levels of serum resistin are associated with inflammation, higher global disease activity index and muscle injury in patients with myositis-specific anti-Jo-1 antibody and patients with dermatomyositis. Furthermore, up-regulation of resistin in muscle tissue and resistin-induced synthesis of pro-inflammatory cytokines in mononuclear cells suggest a potential role for resistin in the pathogenesis of inflammatory myopathies.
Keywords: Resistin; Male; myozitida; Myositis; lidé; imunohistochemie; mužské pohlaví; ženské pohlaví; kvantitativní polymerázová řetězová reakce; lidé středního věku; resistin; Female; Immunohistochemistry; Real-Time Polymerase Chain Reaction; Humans; Middle Aged